2015
DOI: 10.1080/02650487.2014.996199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of underdog (vs. top dog) positioning advertising

Abstract: The study investigates individual differences in attitudes towards brands being positioned as underdogs in advertising from an emotional perspective. We argue that the personality trait of empathic concern moderates the underdog effect on brand attitude and that the moderating effect is mediated by empathic response to the advertisement. We conducted three experiments with ads using top-dog and underdog appeals. Those who have stronger empathic concern showed more favourable attitudes towards the brand adverti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 57 publications
5
47
0
Order By: Relevance
“…Moreover, it would be interesting whether such appeals to local consumer culture can work for smaller companies or so-called underdog brands (Jun et al, 2015). To date, such strategies have not been tried very often so it is difficult to know.…”
Section: ) Sexual Appeals Have Become Relatively Rarementioning
confidence: 99%
“…Moreover, it would be interesting whether such appeals to local consumer culture can work for smaller companies or so-called underdog brands (Jun et al, 2015). To date, such strategies have not been tried very often so it is difficult to know.…”
Section: ) Sexual Appeals Have Become Relatively Rarementioning
confidence: 99%
“…This positive attitude also influences consumer choices as the perceived value and preference of those brands increase (Salehzadeh and Pool, 2017; Moriuchi and Jackson, 2017; De Cannière et al , 2009; Sheth et al , 1991). Recent research has shown that brand positioning emphasizing the disadvantageous, less privileged condition of a brand (underdog) has been used in practice and has continuously gained research interest (Shirai, 2017; Kao, 2015; Jun et al , 2015; Paharia et al , 2010, 2014). The underdog brand biography by Paharia et al (2010) is one of the most commonly employed in business.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a growing body of research has explored the domains in which we offer support for underdogs. Businesses marketing themselves as underdogs facilitate support and greater buying intentions from consumers as a result of heightened identification with the brand (Jun, Sung, Gentry, & McGinnis, 2015; Paharia et al, 2011). People also express an increased desire to vote for political candidates they describe as underdogs (Goldschmied & Vandello, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, all straightforward tests of the underdog effect result in heightened support and interpersonal evaluations. Additionally, people evaluate the underdog’s product more favorably (e.g., Goldschmied et al, 2017; Jun et al, 2015), though not always (e.g., Kim et al, 2008). Consequently, we explore here whether or not people more favorably evaluate music ostensibly composed by underdogs (versus topdogs).…”
Section: Introductionmentioning
confidence: 99%